PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN (Studi terhadap Bendahara Pemerintah pada Badan Pengelola Pendapatan Daerah Provinsi Jawa Tengah) - Anindhiati Restu Wardhani; Daljono Daljono (Diponegoro Journal of Accounting, 2020)
This study examines the level of compliance of corporate taxpayers in paying corporate tax within the Central Java Regional Revenue Management Agency by using several independent variables including tax knowledge, tax socialization, tax sanctions. The dependent variable in this study is taxpayer compliance. In this study aims to analyze the influence of tax knowledge, tax socialization, and tax sanctions on corporate taxpayer compliance. The population of this study is corporate taxpayers, especially the Government Treasurer in the Central Java Regional Revenue Management Agency. The sample uses a saturated sample method which amounts to 41 respondents. Data collection techniques were carried out using a questionnaire. Analysis of research data using multiple linear analysis with SPSS 25.0 program. The results of this study indicate that tax knowledge and tax sanctions have a significant positive relationship on taxpayer compliance. While tax socialization has a negative relationship with taxpayers.